2005
DOI: 10.1096/fj.04-2578fje
|View full text |Cite
|
Sign up to set email alerts
|

Altered proteasome structure, function, and oxidation in aged muscle

Abstract: The proteasome is the main protease for degrading oxidized proteins. We asked whether altered proteasome function contributes to the accumulation of oxidized muscle proteins with aging. Proteasome structure, function, and oxidation state were compared in young and aged F344BN rat fast-twitch skeletal muscle. In proteasome-enriched homogenates from aged muscle, we observed a two- to threefold increase in content of the 20S proteasome that was due to a corresponding increase in immunoproteasome. Content of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
199
6
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(216 citation statements)
references
References 54 publications
(72 reference statements)
9
199
6
2
Order By: Relevance
“…Total proteasome content was determined from the immune reactions of the α6 or α7 subunits of the 20S core. The α-subunits are part of the constitutive complex and therefore, provide a valid estimate of the total content (Ferrington et al, 2005;Husom et al, 2004). Densitometric analysis of the immunoreaction revealed no age-dependent change in proteasome content in both the retina ( Figure 2A) and RPE ( Figure 2B).…”
Section: Analysis Of Proteasome Content and Subunit Compositionmentioning
confidence: 96%
See 1 more Smart Citation
“…Total proteasome content was determined from the immune reactions of the α6 or α7 subunits of the 20S core. The α-subunits are part of the constitutive complex and therefore, provide a valid estimate of the total content (Ferrington et al, 2005;Husom et al, 2004). Densitometric analysis of the immunoreaction revealed no age-dependent change in proteasome content in both the retina ( Figure 2A) and RPE ( Figure 2B).…”
Section: Analysis Of Proteasome Content and Subunit Compositionmentioning
confidence: 96%
“…Association of the regulatory complexes, PA28 and PA700, with the 20S catalytic core has been shown to increase proteasome activity (DeMartino et al, 1996;Dubiel et al, 1992;Ferrington et al, 2005;Reidlinger et al, 1997). Using antibodies that recognize the α-subunit of PA28 and the S4 subunit of PA700, we evaluated the content of these proteasome activators in the retina and RPE.…”
Section: Content Of Regulatory Complexesmentioning
confidence: 99%
“…Protein misfolding can further originate from direct protein damage (e.g., oxidation, thermal denaturation), but can also originate from age‐related mutations, molecular misreading (van Leeuwen et al ., 2000), splicing errors (Pettigrew & Brown, 2008), or errors in translation (Parker, 1989; Kramer & Farabaugh, 2007). While cells are challenged by an accumulation of oxidized, misfolded, and aggregation‐prone proteins, their capacity to deal with accumulated protein damage declines with aging (Liu et al ., 1989; Bulteau et al ., 2002; Ferrington et al ., 2005; Naidoo et al ., 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Decreased proteasome activity in human muscles is age‐associated,12 whereas in rats, proteasome activity in muscles increases with age 13. We reported that proteasome activity is reduced in a mouse model for muscle ageing 14.…”
Section: Introductionmentioning
confidence: 88%
“…Despite the prominent role of the proteasome in maintaining protein homeostasis in muscles, the changes in proteasomal activity with age are not fully understood. In most studies, measurements of proteasomal activity in muscles and in muscle cell culture are carried out predominantly by low‐throughput biochemical assays 12, 15, 16. Robust and accurate measurement of proteasomal activity could report altered myogenesis and muscle function.…”
Section: Introductionmentioning
confidence: 99%